Caspase Mediated Cleavage, IAP Binding and Ubiquitination: Linking Three Mechanisms Crucial for Drosophila NF-κB Signaling - Paquette, Nicholas (2010)
Innate immune responses are critical for the immediate protection against microbial infection. In Drosophila, infection leads to the rapid and robust production of antimicrobial peptides, through two NF-κB signaling pathways - IMD and Toll. The IMD pathway is triggered by DAP-type peptidoglycan, common to most Gram-negative bacteria. Signaling downstream from the peptidoglycan receptors is thought to involve K63-ubiquitination and caspase-mediated cleavage, but the molecular mechanisms remain obscure. We now show that PGN-stimulation causes caspase-mediated cleavage of the imd protein, exposing a highly conserved IAP-binding motif (IBM) at its neo-N-terminus. A functional IBM is required for the association of cleaved-IMD with the ubiquitin E3 ligase DIAP2. Through its association with DIAP2, IMD is rapidly conjugated with K63-linked polyubiquitin chains. These results mechanistically connect caspase-mediated cleavage and K63-ubiquitination in immune-induced NF-κB signaling.